Cutting balloon angioplasty on branch pulmonary artery stenosis in pediatric patients. Issue 3 (10th June 2021) - Cobb, Harrison; Spray, Beverly; Daily, Joshua; Dossey, Amy; Angtuaco, Michael J.
Abstract: Objectives: To identify medium‐term results following cutting balloon angioplasty (CBA) for branch pulmonary artery stenosis (PAS) and predictors of successful intervention. Background: CBA has emerged as a successful alternative therapy for PAS resistant to conventional balloon angioplasty techniques but there is little information on medium and long‐term outcomes. Methods: This is a descriptive, single center, retrospective chart review of pediatric patients who underwent CBA for PAS at Arkansas Children's Hospital between May 2005 and December 2020. We reviewed demographics, procedural specifics, and 30‐day complications. Results: Forty‐four patients underwent pulmonary artery CBA on 114 pulmonary artery segments through 126 catheterization cases, totaling 148 CBA events. Thirty‐three individual pulmonary arteries underwent repeat intervention. Average minimal luminal diameter increase from pre‐CBA to end of follow‐up was 57% (CI, 38%–75%). Absence of Tetralogy of Fallot with pulmonary atresia and major aortopulmonary collateral arteries (TOF/PA/MAPCAs) and the absence of Alagille Syndrome, Williams Syndrome, or Arterial Tortuosity Syndrome (ATS) were associated with increased odds of sustained success by 70% (CI, 0.11–0.79) and 91% (CI, 0.02–0.56), respectively. Increasing the cutting balloon diameter‐to‐minimal luminal diameter ratio by 0.5 increased odds of successful intervention by 2.37‐fold (CI, 1.7–3.3). Seven patients had 30‐day complications including one death. Conclusions: In the longest follow‐up to date of children and adolescents who underwent CBA for branch PAS, we found that there was moderate medium‐term success. Additionally, absence of TOF/PA/MAPCAs, absence of Alagille Syndrome, Williams Syndrome, or ATS, and high cutting balloon diameter‐to‐minimal luminal diameter ratio are predictors of sustained results.